Optimizing UAV operation parameters for enhanced pesticide deposition in tobacco fields - Li, Tianliang; Miao, Pu; Wang, Jing; Li, Chengjun; Wang, Guiyao; Sun, Xiaowei; Zhao, Te (Frontiers in Agronomy, 2025)
IntroductionUnmanned aerial vehicles (UAVs) have rapidly developed as efficient plant protection machinery and are widely used for pesticide application across complex terrains. However, optimal operating parameters for UAV spraying in tobacco fields remain insufficiently defined across different growth stages.MethodsThis study assessed the spraying performance of two UAV models, T20P and T40, under multiple combinations of flight height, flight speed, and spray volume. Experiments were conducted during the rosette stage, vigorous growth stage, and maturity stage of tobacco plants. Using a multi-index weighted analysis method, the optimal combinations of operational parameters for different tobacco growth stages were evaluated.Results and DiscussionThe results indicated that variations in operational parameters significantly affected the deposition and distribution of droplets. For T20P, the optimal parameters for the rosette stage were a flight speed of 3 m•s-1, a flight height of 2 m, and a spray volume of 50 L•ha-1. During the vigorous growth stage, the optimal parameters were a flight height of 2.5 m, a flight speed of 4 m•s-1, and a spray volume of 50 L•ha-1. For the maturity stage, the parameters were a flight height of 2.5 m, a flight speed of 3 m•s-1, and a spray volume of 50 L•ha-1. For T40, the optimal parameters for the rosette stage were a flight height of 3 m, a flight speed of 3 m•s-1, and a spray volume of 50 L•ha-1. During the vigorous growth stage, the parameters were a flight height of 3.5 m, a flight speed of 4 m•s-1, and a spray volume of 50 L•ha-1. For the maturity stage, the parameters were a flight height of 3.5 m, a flight speed of 3 m•s-¹, and a spray volume of 50 L•ha-1. By applying these optimized parameters at the corresponding growth stages, a balanced spray performance can be achieved, thereby maximizing pesticide utilization. These findings provide a practical reference for improving droplet deposition and enhancing the effectiveness of UAV pesticide application in tobacco production.